Data aggregation scheduling algorithm based on twice maximum independent set - Jian XU; Geng YANG; Zheng-yu CHEN; Hai-yong WANG; Zhen YANG (Tongxin xuebao)
The main task in designing a data aggregation schedule was to get a good trade-off between QoS and weighted fairness guarantee.In order to address this problem,a novel data aggregation scheduling algorithm,MISS,was proposed,which could produce a collision-free TDMA schedule for data aggregation based on twice Maximum Independent Set (MIS).In the first phase,a tree structure based on MIS was constructed,and then it was adjusted according to the energy consumption forecast of each node,forming the balanced data aggregation tree.In the second phase,the approximate maximum weighted Independent set (WMIS) was utilized of all selected links to allocate time slots for each communication link.The results of simulation demonstrate that MISS not only improves the aggregation delay and lifetime of the network,but also gives weighted fairness guarantee.